KEBERADAAN KOMISI APARATUR SIPIL NEGARA KAITANNYA DENGAN ASAS EFEKTIF DAN EFISIEN DALAM UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Herdiansyah Putra, Eddy Purnama, Taqwaddin. (Jurnal Ilmu Hukum, 2015)
Abstract : The existence of the Civil Servant Commission (CSC or abbreviated KASN in bahasa), its own function, tasks, authority had been extensively studied in this research. Hence, its main objectives to monitor and to evaluate several aspects, e.g. policy-implementation, civil servants’ management, a guaranteed of an embodied merit system, the monitoring of basic law’s implementation, ethical- and behavioral-codes among the civil servants employed by the Republic of Indonesia were also being reviewed. The CSC’s location, particularly, at the country’s capital city was regarded here as the main challenge and obstacles in term of its effectiveness in carrying its own duties. The aim of this study is to determine whether the CSC’s working principles was in accordance with the effectiveness and efficiency principles. Moreover, other similar regulation, e.g. Law Number 5/ Year 201 that explained about civil servants, might be hindered CSC in implementating of its function, tasks, and authority. Research methodology applied was normative juridical research. The indicators showed that the CSC had not yet optimally worked in accordance with the effectiveness and efficiency principles in carrying its own duties, such as by the hiring of leading positions, an exceed number of leading positions compared with the total number of area, a contradicted legislation regarding the management of regional government e.g. Article 375/ Paragraph 3 of Act No. 23/ Year 2014. This stated that the governor, himself, acts as a central government’s representative and he is responsible in supervising public issues, including civil servant management at regional level. This study recommends that the Indonesian government needs to maximize the CSC’s existence, to immediately recruit supporting staffs, or to form CSC at regional levels, so that it could meet its requirment to reach an optimum function, task, and authority. Furthermore, it is also immediately recommended to harmonize and to reach a common understanding by the hiring of leadership position.Keywords : civil servant management, Indonesian government, the civil servant commission. Abstrak: Keberadaan Komisi Aparatur Sipil Negara [disingkat dengan KASN (indonesia) atau CCS (inggris)] dengan fungsi, tugas, dan kewenangan dipelajari secara ekstensif dalam penelitian ini. Untuk itu, tujuan utama pembentukannya untuk melakukan monitoring dan evaluasi beberapa aspek, seperti pelaksanaan kebijakan, manajemen Aparatur Sipil Negara (ASN), penjaminan perwujudan sistem merit, serta pengawasan terhadap penerapan asas, kode etik dan perilaku diantara ASN Republik Indonesia juga direview. Letak KASN, khususnya yang berkedudukan di ibu kota negara dianggap sebagai tantangan dan hambatan sehubungan dengan kefektifan dalam menjalankan tugasnya. Tujuan penelitian ini untuk memastikan apakah prinsip kerja KASN sesuai dengan asas efektif dan efisien. Selain itu, peraturan sejenis, seperti Undang-Undang Nomor 5 Tahun 2014 tentang Aparatur Sipil Negara dapat menjadi hambatan bagi KASN dalam melaksanakan fungsi, tugas dan kewenangan. Metode penelitian yang digunakan adalah penelitian yuridis normatif. Indikator menunjukan bahwa KASN belum bekerja secara optimal sesuai asas efektif dan efisien dalam melakukan tugasnya, seperti dalam pengisian jabatan pimpinan tinggi, banyaknya jumlah jabatan pimpinan tinggi dibanding dengan luas wilayah, adanya kontradiksi pengaturan perundangan mengenai tata laksana pemerintah daerah, seperti pasal 375 ayat (3) Undang-Undang Nomor 23/ Tahun 2014. Disini disebutkan bahwa Gubernur merupakan wakil pemerintah pusat dan bertanggung jawab dalam pembinaan yang bersifat umum, termasuk tata laksana kepegawaian pada perangkat daerah. Studi ini menyarankan pemerintah Indonesia untuk memaksimalkan keberadaan KASN, segera melakukan perekrutan tenaga pendukung, atau untuk membentuk KASN di daerah, sehingga KASN dapat bekerja secara optimal dalam melaksanakan fungsi, tugas, kewenangan. Selain itu, studi ini juga segera merekomendasikan untuk mengharmonisasi dan mencapai kesamaan pemahaman terkait dengan pengaturan pengisian jabatan pimpinan tinggi.Kata kunci: tata laksana aparatur sipil negara, hukum pemerintahan Indonesia, Komisi Aparatur Sipil Negara.